Modulation in Elastic Properties of Upper Trapezius with Varying Neck Angle. (3rd March 2019) - Zhang, Jun; Yu, Jiafeng; Liu, Chunlong; Tang, Chunzhi; Zhang, Zhijie
Abstract : Background . Neck and shoulder complaints caused by poor posture may influence upper trapezius stiffness. The relationship between the shear elastic modulus of the upper trapezius and cervical flexion angles is unknown. Therefore, it is essential to assess upper trapezius stiffness during cervical flexion. The objectives of this study were to (1) determine the intra- and interoperator reliabilities of evaluating upper trapezius stiffness and calculate the minimal detectable change (MDC); (2) examine the elastic modulus alterations of the upper trapezius during cervical flexion; and (3) explore the difference of upper trapezius stiffness between the dominant and nondominant sides. Methods . Twenty healthy male participants were recruited in this study. The shear modulus of the upper trapezius was evaluated by two independent investigators using shear wave elastography (SWE) during cervical flexion at 0° and 50°. Findings . The intraoperator (intraclass correlation coefficient ICC = 0.85 –0.86) and interoperator (ICC = 0.94 –0.98) reliabilities for measuring the shear elastic modulus of the upper trapezius during the cervical flexion ranged from good to excellent. An increase of 35.58% in upper trapezius stiffness was found at 0° to 50° of cervical flexion, and the MDC was 7.04 kPa. In addition, a significant difference was obtained in the elastic modulus of the upper trapezius muscle between the dominant and nondominant sides (P < 0.05 ). Conclusions . Our findings revealed that SWE could quantify the elastic modulus of the upper trapezius and monitor its changes. Therefore, further studies are required to delineate the modulation in upper trapezius muscle stiffness among subjects with neck and shoulder pain.